Dexamethasone ameliorates H2S-induced acute lung injury by increasing claudin-5 expression via the PI3K pathway. (June 2018) - Geng, P; Ma, T; Xing, J; Jiang, L; Sun, H; Zhu, B; Zhang, H; Xiao, H; Wang, J; Zhang, J
Acute lung injury (ALI) is a major outcome of exposure to high levels of hydrogen sulfide (H2 S). Dexamethasone (DXM) has been used to treat ALI. However, the mechanisms involved in H2 S-induced ALI and the protective mechanisms of DXM in treating ALI are still nebulous. To explore the mechanisms involved, we evaluated the role of claudin-5 in the protective effect of DXM against H2 S-induced ALI. Sprague-Dawley rats were exposed to H2 S to establish the ALI model. In parallel with the animal model, a cell model was also established by incubating human umbilical vein endothelial cells (HUVECs) with NaHS. Lung hematoxylin–eosin staining, electron microscope assay, and wet/dry ratio were used to identify whether the ALI was successfully induced by H2 S, and changes in claudin-5 expression were detected in both rats and HUVECs. Our results revealed that claudin-5 was markedly decreased after H2 S exposure and that DXM significantly attenuated the H2 S-induced downregulation of claudin-5 in both rats and HUVECs. In the animal experiment, p-Akt and p-FoxO1 presented a similar tendency as claudin-5, but their levels decreased 6 h prior to the levels of claudin-5. In a further investigation, the DXM-induced protective effect on ALI and rescue effect on downregulation of claudin-5 were both blocked by LY294002. The current study demonstrated that claudin-5 was involved in the development of H2 S-induced ALI and that DXM exerted protective effects through increasing claudin-5 expression by activating the phosphatidylinositol 3-kinase pathway. Therefore, claudin-5 might represent a novel pharmacological target for treating ALI induced by H2 S and other hazardous gases.